Dynamic analysis of exchange rate regimes: Policy implications for emerging countries in Asia - Naoyuki Yoshino; Sahoko Kaji; Tamon Asonuma (Asian Development Bank Institute (ADBI), 2014)
This paper discusses desirable exchange rate regimes and how countries can shift from their current regimes to these regimes over the medium term. We demonstrate the superiority of a basket-peg regime with the basket weight rule over a floating regime with the interest rate rule or the money supply rule in small open economies, during periods when volatility of exchange rates is moderate. Countries which currently have fixed exchange rates would be better moving toward either a basket-peg or a floating regime over the medium term. A shift to a basket-peg regime is preferred when exchange rate fluctuations are large.
Keywords: E42; F33; F41; F42; 330; exchange rate regimes; basket-peg; floating regime; interest rate rules